IMPACT ADDICTED SOCIAL MEDIA ON TEENAGER IN PALEMBANG CITY - Sefty Anggraini; Ris’an Rusli; Fajar, Fajar Tri Utami (CV. Era Digital Nusantara, 2022)
This study aims to describe the impact of social media addiction on adolescents in the city of Palembang. The method used in this research is a qualitative research method with a descriptive design. The subjects in this study were 3 women who were students using purposive sampling. Furthermore, the data collection method uses interviews, observation, and documentation. Meanwhile, data analysis uses data collection, data reduction, data display, and conclusion / verification. The results of this study indicate that there are positive impacts and negative impacts felt by the three subjects. The negative impact is a lot of time spent on social media, decreased achievement at school, less active in the social environment. The positive impact makes it easier for subjects to communicate. The results of this study also show that social media addiction has more negative effects that positive effects.